A meta-synthesis study in interactive learning environments: digital games in health education - Efe, Hacer; Umdu Topsakal, Unsal (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
Interactive learning environments are new generation learning environments that support the use of technology in education. The most popular and most entertaining of these technological learning environments are digital games. Within the scope of the study, digital games and health education related keywords were searched in ProQuest, Web of Science and Google Scholar databases. In the study, which focused on the years 2015-2021, a total of 557 articles were reached and 23 articles the inclusion criteria in line with the criteria determined before the research. Various age groups were examined in the studies. Design-based research has been carried out mostly in the field of sexual health education. The results show that the effects of the use of digital games in health education on participants' health knowledge and health literacy, health motivation and attitude, health self-efficacy and self-awareness, and participants' views on game usability and game experience were examined. In addition, it was stated in some studies that the health status of participants who played digital health games improved. In all of the studies examined in the current meta-synthesis, positive results were obtained in the use of digital games in health education. The article ends with the identification of gaps in the literature and recommendations for additional research.
Keywords: Interactive learning environments; digital games; meta-synthesis; research; health education; LIFE; Education & Educational Research